Pemberian Informasi Obat Pasien Dengan Resep Antibiotik dan Penyediaan Antibiotik Tanpa Resep di Tangerang Selatan: Providing Drug Information to Patients with Prescribing Antibiotics and Provision of Antibiotics without Prescription in South Tangerang - Saibi, Yardi; Suryani, Nelly; Novitri, Suci Ahda; Hasan, Delina; Anwar, Vidia Arlaini (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
A pharmacy is a place where pharmacists do their pharmaceutical work, serving directly and responsibly for patients who need their professional services. One form of direct service is the provision of drug information and counseling. The purpose of this study was to describe the drug information services provided by pharmaceutical personnel in the South Tangerang area pharmacy for patients who redeemed prescriptions using antibiotics. Patient simulation method was used to collect data to 100 pharmacies that were randomly selected based on data in the city health office. Recommendations were obtained from the South Tangerang branch of the Indonesian Pharmacists Association while ethical clearance was obtained from the ethical committee of the Faculty of Medicine, University of Indonesia. The results of this study indicate that 85% percent of pharmaceutical personnel who provide drug information for simulated patients are non-pharmacists. The most widely conveyed drug information items were the frequency of drug use delivered by 82% of pharmacists, received by the intended use (61%) and time of use (44%). Not related to pharmacy officers who submit the following information: drug interactions and ways to prevent them, side effects of drugs and how to prevent them; food and drinks that must be avoided as well as how to store drugs. As many as 49% of pharmacists provide additional antibiotics requested by patients without a prescription. Drug information points provided by pharmacy staff specifically by pharmacist had not been maximally delivered.